Legal Regulation of Surrogacy in Poland and Ukraine – a Comparative Analysis - Sarnacka, Emilia; Demchenko, Ivan (Review of European and Comparative Law, 2024)
The paper focuses on surrogacy regulation, which is diverse across European countries. Four categories of rules can be identified, namely: absence of regulation, regulations allowing surrogacy , regulations that do not allow it with ongoing discussion about allowing it, and regulations under which surrogacy is strictly forbidden. Poland and Ukraine are neighboring countries with radically different regulations on surrogacy. There is no direct regulation on surrogacy in Poland and it can be stated that surrogacy agreements are not valid. IVF procedure is strictly forbidden for surrogacy. Ukraine is an example of the most liberal country when it comes to surrogacy regulation. Surrogacy agreements are regulated and requirements are formulated for surrogate mothers. Ukrainian regulation allows remuneration for surrogate mothers. After the Russian invasion, Ukrainian surrogate mothers came to Poland looking for safety. The Polish state provided extensive support for the Ukrainian people, including specific legal regulation on the right to access health care and employment opportunities. Yet, the Ukrainian surrogacy agreements are not valid in Poland, and the surrogate mothers will be approved as legal mothers.